2013
DOI: 10.2478/s11756-013-0294-z
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase inhibitory potential of different Alternaria spp. and their phylogenetic relationships

Abstract: Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitors are used for the treatment of various disorders related to decline in acetylcholine levels in the brain by inhibiting the activity of the neurotransmitter AChE. The present study reports the potential of endophytic Alternaria spp. for their potential to produce cholinesterase inhibitors active against both acetylcholine and butyrylcholine. Twenty-nine isolates belonging to Alternaria spp. were isolated from different plants and screened. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The fungi produced a wide range of secondary metabolites that can contribute positively in an agricultural context against several pests [43]. Among them the acetylcholinesterase inhibitory molecules could be applied in agriculture to control insects and other arthropod pests [44], by acting against their nervous systems [45] and increasing their acetylcholine level which induces a repetitive activity of the neurons leading to the death of the insect [46]. In comparison with our study, a 70%…”
Section: Discussionmentioning
confidence: 57%
“…The fungi produced a wide range of secondary metabolites that can contribute positively in an agricultural context against several pests [43]. Among them the acetylcholinesterase inhibitory molecules could be applied in agriculture to control insects and other arthropod pests [44], by acting against their nervous systems [45] and increasing their acetylcholine level which induces a repetitive activity of the neurons leading to the death of the insect [46]. In comparison with our study, a 70%…”
Section: Discussionmentioning
confidence: 57%
“…Although various bioactivities such as antimicrobial and cytotoxicity have been reported from endophytic A. alternata isolated from different plants (Devari et al 2014;Wang et al 2014;Kamal et al 2015), there are very few reports on AChE inhibition. Singh et al (2014) demonstrated dual cholinesterase inhibitory activity in Alternaria spp isolated from different plants. It has been suggested that the use of dual cholinesterase inhibitors for both AChE and BuChE as targets, may prove more effective in treating patients with AD, hence increasing their potential as pharmaceutical agents.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al . () demonstrated dual cholinesterase inhibitory activity in Alternaria spp isolated from different plants. It has been suggested that the use of dual cholinesterase inhibitors for both AChE and BuChE as targets, may prove more effective in treating patients with AD, hence increasing their potential as pharmaceutical agents.…”
Section: Discussionmentioning
confidence: 99%
“…and these results were compared with standard drug Galantamine ( Table 7). The inhibition of these enzymes may be due to the C. uredinicola phytochemicals may adsorbed or interact with AChE or BChE protein [44][45]. The molecular interaction studies were carried out between C. uredinicola phytochemicals with oxidant, HIV-1, diabetes and acetyl-cholinesterase proteins.…”
Section: Treating Agentsmentioning
confidence: 99%